Pengaruh Kebijakan Dividen Terhadap Kinerja Keuangan pada PT. Gudang Garam TB - Sitti Maryam; Abdullah Abdullah; Ihsan Guntur (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Multinational companies in Indonesia, such as PT Gudang Garam Tbk, with complex financial statements, are interesting subjects for study. The company's capital ownership has increased annually, but this growth has not been accompanied by an increase in profits. The analysis is based on the financial statements of PT Gudang Garam Tbk for the period 2018-2022, using simple regression analysis. In this analysis, the dividend payout ratio, Return On Investment, and Return On Equity are considered as independent variables (x), while financial performance is the dependent variable (y). The study results show an increase in the dividend policy, but a decrease in ROI and ROE. Furthermore, the statistical analysis reveals that the dividend policy has a positive effect on financial performance, while ROI and ROE have a negative impact on financial performance. The findings indicate that the low profit growth is not due to high or low capital, but is instead caused by the return on investment (ROI) and return on capital (ROE) in the form of profit sharing. Hence, it is the return process that leads to declining or low profits.